(untitled) (Research, Society and Development, 2026)
Introduction: Alzheimer’s disease (AD) is the most frequent progressive neurodegenerative disorder among older adults, being the leading cause of dementia and impairments related to cognition and memory in this population. The present study aims to conduct an epidemiological analysis of AD cases in Northeast Brazil, describing and analyzing hospitalizations between 2019 and 2023 in order to contribute to the understanding and management of this condition, which significantly affects the quality of life of the elderly population. Materials and Methods: This is a descriptive cross-sectional epidemiological study conducted using data available from the Department of Informatics of the Unified Health System (DATASUS). The variables analyzed were: state, sex, and age group. Results: The epidemiological analysis revealed a significant increase in the number of hospitalizations from 2019 to 2023, highlighting the impact of the COVID-19 pandemic on access to healthcare services for this population, thereby increasing their already existing vulnerability. The most affected profile was women over 80 years of age. The main causes of hospitalization were respiratory and/or urinary complications, swallowing disorders associated with consequent malnutrition, and polypharmacy. A marked need for improvements in home care was also identified, aiming to prevent new hospital admissions. Conclusion: More effective health actions are required to reduce the number of hospitalizations due to AD, as well as a more comprehensive notification process by healthcare professionals to support future research.